Efficiency of immunoglobulin G replacement therapy in common variable immunodeficiency: correlations with clinical phenotype and polymorphism of the neonatal Fc receptor. (3rd January 2013) - Gouilleux‐Gruart, V.; Chapel, H.; Chevret, S.; Lucas, M.; Malphettes, M.; Fieschi, C.; Patel, S.; Boutboul, D.; Marson, M.‐N.; Gérard, L.; Lee, M.; Watier, H.; et al.
Summary Treatment of common variable immunodeficiency disorders (CVID) is based on replacement therapy using intravenous (i.v.) or subcutaneous (s.c.) immunoglobulin (Ig)G. Interindividual variation of IgG dose is common. A total of 380 CVID patients on stable IgG replacement from two prospective cohorts were analysed. An 'efficiency' index was defined as the ratio of serum IgG trough level minus IgG residual to the average weekly dose of IgG infusion. A reduced efficiency of IgG was associated independently with the i.v. route (P < 0·001) and with the presence of at least one CVID disease‐related phenotype (lymphoproliferation, autoimmune cytopenia or enteropathy) (P < 0·001). High IgG efficiency was noted in patients homozygotes for the variable number tandem repeat (VNTR) 3/3 polymorphism of the neonatal Fc receptor gene [IgG Fc fragment receptor transporter alpha chain (FCGRT)] promoter, and this was particularly significant in patients treated with IVIG (P < 0.01). In a multivariate analysis, FCGRT VNTR 3/3 genotype (P = 0·008) and high serum albumin (P < 0·001) were associated independently with increased efficiency of i.v. Ig.